MALT-lymphoma of the stomach: clinical presentation, diagnostics and treatment - Ye. V. Ledin; A. P. Seryakov; V. L. Astashov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present up-to-date data on diagnostics and treatment of MALT-lymphoma of the stomach and experience of N.N.Burdenko Chief military clinical hospital in treatment of patients with this disease.Original positions. Not so long ago mucosa-associated lymphoid tumor was included in WHO classification of hemopoietic and lymphoid tissues tumors, which is terminologically determined as extranodal marginal zone В-cellular lymphoma of the MALT-type. It is proved, that approximately 90% of cases of stomach МАLT-lymphomas are related to H. pylori infection. Despite the extensive data obtained for the last two decades on clinical and pathomorphologic properties of this disease, its molecular genetic features, optimal medical approach for this nosological entity it is not developed yet. It is especially actual for regional stages of disease. The article stresses therapeutic aspects: correspondence of treatment approach to disease stage, presence of Н. pylori infection, role of eradication and radiation therapy, surgery and chemotherapy. Basing on obtained data, original treatment algorithm was developed, which is proposed to application in clinical practice to provide optimal amount of medical care to the patient.Conclusion. Findings in MALT-lymphoma biology allowed to introduce new scientific and practical treatment projects in practice.